Outcome of aplastic anaemia in children. A study by the severe aplastic anaemia and paediatric disease working parties of the European group blood and bone marrow transplant. (14th February 2015) - Dufour, Carlo; Pillon, Marta; Sociè, Gerard; Rovò, Alicia; Carraro, Elisa; Bacigalupo, Andrea; Oneto, Rosi; Passweg, Jakob; Risitano, Antonio; Tichelli, Andrè; Peffault de Latour, Regis; Schrezenmeier, Hubert; et al.
Summary: This study analysed the outcome of 563 Aplastic Anaemia (AA) children aged 0–12 years reported to the Severe Aplastic Anaemia Working Party database of the European Society for Blood and Marrow Transplantation, according to treatment received. Overall survival (OS) after upfront human leucocyte antigen‐matched family donor (MFD) haematopoietic stem cell transplantation (HSCT) or immunosuppressive treatment (IST) was 91% vs. 87% ( P 0·18). Event‐free survival (EFS) after upfront MFD HSCT or IST was 87% vs. 33% ( P 0·001). Ninety‐one of 167 patients (55%) failed front‐line IST and underwent rescue HSCT. The OS of this rescue group was 83% compared with 91% for upfront MFD HSCT patients and 97% for those who did not fail IST up‐front ( P 0·017). Rejection was 2% for MFD HSCT and HSCT post‐IST failure ( P 0·73). Acute graft‐ versus ‐host disease (GVHD) grade II‐IV was 8% in MFD graft vs. 25% for HSCT post‐IST failure ( P < 0·0001). Chronic GVHD was 6% in MFD HSCT vs. 20% in HSCT post‐IST failure ( P < 0·0001). MFD HSCT is an excellent therapy for children with AA. IST has a high failure rate, but remains a reasonable first‐line choice if MFD HSCT is not available because high OS enables access to HSCT, which is a very good rescue option.